2008
DOI: 10.1016/j.ejcts.2008.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for aortic insufficiency and aortic valve replacement after the arterial switch operation☆

Abstract: The incidence of trivial or mild AI after the ASO is considerable and a progression over time is evident. However, severe AI and the need for AVR are rare. Patients with VSD or Taussig-Bing anomaly, and those with left ventricular outflow tract obstruction exhibit a higher risk of developing significant aortic insufficiency. Particularly patients who have developed an AI at 1 year after the ASO need to be under close observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 23 publications
7
50
1
4
Order By: Relevance
“…15 Patients with Taussig-Bing anomaly and other forms of double outlet right ventricle have a higher risk of developing significant AI and of requiring aortic valve replacement compared with patients with transposition of the great arteries. 16,17 Prior pulmonary artery banding (which may distort and increase flow velocity across the native pulmonary valve), older operative age, and higher operative weights have previously been associated with the development of significant AI in Taussig-Bing anomaly, 6 which further supports singlestage repair as a possible protective strategy. In this cohort, we demonstrated a low rate of significant AI after primary ASO.…”
Section: Neoaortic Insufficiencymentioning
confidence: 92%
“…15 Patients with Taussig-Bing anomaly and other forms of double outlet right ventricle have a higher risk of developing significant AI and of requiring aortic valve replacement compared with patients with transposition of the great arteries. 16,17 Prior pulmonary artery banding (which may distort and increase flow velocity across the native pulmonary valve), older operative age, and higher operative weights have previously been associated with the development of significant AI in Taussig-Bing anomaly, 6 which further supports singlestage repair as a possible protective strategy. In this cohort, we demonstrated a low rate of significant AI after primary ASO.…”
Section: Neoaortic Insufficiencymentioning
confidence: 92%
“…The presence of aortic root dilatation has been demonstrated in up to 60% to 70% of patients after ASO; nonetheless, it does not tend to be progressive during late follow-up. Conversely, the progression of the degree of neoaortic valve insufficiency rarely occurs during the first 10 to 15 years after ASO, but it was found that it increases significantly later, and this is associated with the degree of postoperative neoaortic valve insufficiency at discharge soon after ASO [14,20,21]. Anatomic causes identified to be responsible for aortic root dilatation and neoaortic valve insufficiency included the presence of a ventricular septal defect and aortic/pulmonary mismatch and the postoperative geometry of the aortic root [19].…”
Section: Commentmentioning
confidence: 99%
“…The fate of the aorta and aortic valve has been assessed in previous studies. [3][4][5] Most of the patients show nonprogressive dilatation of the aortic root, but few cases experience aortic insufficiency. 6 In addition, reduced proximal aortic elasticity, structural abnormalities of the arterial walls, and increased carotid artery stiffness have been reported in TGA patients.…”
mentioning
confidence: 99%